Saneo Tourism Village Management (Institutional) Training-Community Coaching Approach on Sustainability - Muhammad Sultan Hali; Ramdah Radjab; Firman Koma Febdilan; Ayu Gardenia Lantang; Muhammad Satrio (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Saneo Village as a pioneer village has institutional problems that cause tourism village information on the Kemenparekraf jadesta to be less than optimal, Community involvement plays an important role in encouraging sustainable practices, and this article describes an organizational training program for tourism stakeholders in Saneo Tourism Village which is carried out to support the community that can improve the understanding and commitment of village communities to sustainability. This service method is to provide training to twenty participants with significant increased success results with an average increase of 85%. Community training programs on sustainability have increased Saneo village residents' awareness and involvement in sustainable practices as well as understanding of tourism village organizations. However, this program needs to be improved by considering constraints such as agricultural activities and implementation time. This training succeeded in increasing the institutional knowledge of tourism stakeholders in the village. To further perfect the program, it is necessary to coordinate the implementation time and intensity of tourism stakeholder meetings to improve the quality of tourism human resource development activities in the Saneo Tourism Village.